The effect of GST announcement on stock market volatility: evidence from intraday data - Haron, Razali; Ayojimi, Salami Monsurat (Emerald, 2019)
Purpose – The purpose of this paper is to examine the effect of GST announcements (pre and post) on Malaysian stock market index. This study also utilised intraday data to look into intraday market volatility post-GST announcement. Design/methodology/approach – Both daily closing prices and intraday data of different frequencies are used to capture the extent of stock market volatility as well as the subsided period of the volatility. The period of study ranges from June 2009 to November 2016 and empirical estimation is based on the GARCH (1, 1) model for the pre- and post-GST announcements. Findings – Persistent market volatility in the post-GST announcement is empirically recorded and the volatility is higher in the post-GST announcement than the pre-GST announcement. This demonstrates the unwillingness and reaction of the market towards the tax policy implementation. Market expectation on GST implementation towards the increase in the cost of living following the increase in the prices of goods and services in Malaysia is empirically supported in the post-GST announcement. Practical implications – The finding on this study is consistent with the expectation of the market that GST implementation will increase the price of the goods and services and hence increase the cost of living. This is supported by a noticeable increase in the stock market volatility in the post-GST announcement. Although GST announcement could be classified as a scheduled announcement, unwillingness to accept the policy prevails as shown by the increase in the stock market volatility. Originality/value – The effects of Asian and global financial crisis are the major focus of past studies on stock market volatility, whereas this study examines and highlights the effect of the GST announcement on stock market volatility and the use of intraday data to further examine the nature of the volatility.